2019
DOI: 10.1371/journal.pone.0220943
|View full text |Cite
|
Sign up to set email alerts
|

Crank fore-aft position alters the distribution of work over the push and pull phase during synchronous recumbent handcycling of able-bodied participants

Abstract: Objective The objective of the current study was to investigate the effect of four different crank fore-aft positions on elbow flexion and shoulder protraction, the consequent propulsion kinetics and the physiological responses during handcycling. Methods Twelve able-bodied male participants volunteered in this study. Crank fore-aft positions were standardised at 94%, 97%, 100% and 103% of the participants’ arm length. Two submaximal 3 min trials were performed at a fix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 34 publications
0
13
1
Order By: Relevance
“…The only previous kinetic examinations of recumbent handcycling have been with able-bodied participants, where it has been revealed that greater torque was produced during the pull phase. 20 Whereas the current study identified that independent of crank length, trained handcyclists produced greater torque during the push phase, which highlights why results from able-bodied studies cannot be translated to trained handcyclists. As anticipated, greater mean torque was generated in longer crank lengths.…”
Section: Resultscontrasting
confidence: 53%
See 1 more Smart Citation
“…The only previous kinetic examinations of recumbent handcycling have been with able-bodied participants, where it has been revealed that greater torque was produced during the pull phase. 20 Whereas the current study identified that independent of crank length, trained handcyclists produced greater torque during the push phase, which highlights why results from able-bodied studies cannot be translated to trained handcyclists. As anticipated, greater mean torque was generated in longer crank lengths.…”
Section: Resultscontrasting
confidence: 53%
“…15,16 While this research has largely explored able-bodied participants, the technology offers valuable information to further understand the effects of crank length manipulations. Although previous research has included a combination of kinematic and kinetic measures to examine the effects of different handbike configurations, [17][18][19][20] no study has combined all these measures to investigate trained handcyclists, cycling at sport-specific intensities in a recumbent handbike. Subsequently, the aim of the current study was to explore the impact of crank length on physiological and biomechanical aspects of recumbent handcycling at fixed linear handgrip speeds and sport-specific intensities in highly trained handcyclists.…”
Section: Introductionmentioning
confidence: 99%
“…This is in agreement with previously published studies which have demonstrated that a greater proportion of the work generated during the propulsion cycle of handcycling occurs during the pull phase with an increase in pulling torque and concomitant decrease in pushing torque observed at progressively higher power outputs. 5,27,34 Therefore, based upon these observations it can be inferred that greater relative upper body pulling strength may enhance handcycling performance. Strength training should, therefore, form a central component of any successful handcyclists training programme.…”
Section: Handcycling Performancementioning
confidence: 93%
“…23 Handcycling performance is ultimately dependent upon the physical capabilities of the individual, the design of the handbike, and the interaction between the rider and their equipment, typically referred to as the handbike-user interface. 31 Whilst the biomechanics, 20,27,31 handbike-user interface 4,5,6,22,29,32,34 and physiological characteristics of handcycling performance, namely peak oxygen uptake (V O2peak), peak aerobic power output (POpeak) and gross mechanical efficiency (GME) have been extensively investigated. 1,9,13,19,21,25 To date, only a handful of studies have examined the relationship between the aforementioned physiological characteristics and handcycling race Handcycling Performance performance.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the applied torque over the cycle of the crank of the MRI-compatible handcycle ergometer should ideally also be measured in the MRI scanner. While such systems are available and have been used for arm-cranking and hand-cycling studies (12,33,41), these are as of yet MRI-incompatible. The sole available industrystandard MRI cycle ergometer (Lode BV, Groningen, the Netherlands) could potentially be tted with hardware and software to render such measurements feasible in MRI scanners in the future (Jan-Reinder Franssen, Lode BV, personal communication).…”
Section: Discussionmentioning
confidence: 99%